Kelancaran Produksi ASI pada Ibu Post Partum Ditinjau dari Inisiasi Menyusu Dini dan Isapan Bayi - Yanti, Hellen Febri; Yohanna, Wike Sri; Nurida, Eva (Universitas Aisyah Pringsewu, 2018)
The World Health Organization (WHO) recommends mothers with newborns infant to get colostrum from breast milk on the first and second day to protect and prevent various infections. Presurvey results showed from a total of 135 normal labor, there were 75 infants (55.6 percent) who did not do Early Initiation of Breastfeeding (IMD). This type of research is a quantitative research using analytical survey method, with cross sectional approach. The sample of research is 30 respondents. The result of chi square analysis showed the correlation of Early Initiation of Breastfeeding (IMD) with breastmilk production in post partum mother with p-value 0.009 (p less than 0.05) and OR = 19,000. The result of chi square analysis of baby sucking variable with lactation on post partum mother obtained p-value 0,031, (p less than 0,05) and OR = 12,667. Based on the results of the study can be concluded that the lactation in post partum mothers associated with Initiation of Early Breastfeeding (IMD) and baby sucking. Suggested on post partum mother to increase knowledge such as counseling with health worker about the importance of Early Breastfeeding Initiation and training so that mother's milk production remain smoothly.